2021
DOI: 10.1007/s11605-020-04852-8
|View full text |Cite
|
Sign up to set email alerts
|

A New Quantitative Classification of the Extrahepatic Biliary Tract Related to Cystic Duct Implantation

Abstract: Background Knowledge regarding biliary anatomy and its variations, including the cystic duct (CD), is important in the pre-surgical setting and for predicting biliary diseases. However, no large series has focused on CD evaluation using a quantitative analysis. The primary aim of this prospective study was to create a ‘taxonomic’ classification of CD anatomy in a large cohort of subjects who underwent magnetic resonance cholangiopancreatography (MRCP). The secondary aim was to evaluate the correlations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…An understanding of the anatomy of the biliary tree and its main variations is essential for many reasons, such as providing precise pre‐operative information for surgeons in order to reduce the rate of procedure‐related complications (Farias et al, 2013; Naeem et al, 2020; Sureka et al, 2016). Moreover, accurate knowledge of the biliary system is also required for radiologists since its variations can be associated with biliary tract pathologies and both staging and localization of intrahepatic liver neoplasms and bile duct tumours are based on its segmental anatomy (Medisoglu et al, 2021; Mortelé & Ros, 2001; Mosconi, Solaini, et al, 2021; Renzulli, Brocchi, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of the anatomy of the biliary tree and its main variations is essential for many reasons, such as providing precise pre‐operative information for surgeons in order to reduce the rate of procedure‐related complications (Farias et al, 2013; Naeem et al, 2020; Sureka et al, 2016). Moreover, accurate knowledge of the biliary system is also required for radiologists since its variations can be associated with biliary tract pathologies and both staging and localization of intrahepatic liver neoplasms and bile duct tumours are based on its segmental anatomy (Medisoglu et al, 2021; Mortelé & Ros, 2001; Mosconi, Solaini, et al, 2021; Renzulli, Brocchi, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…CHD plus CBD). Subsequently, these data were used to calculate the CDDP/EHBD ratio and to provide the extra‐hepatic bile duct classification, according to both qualitative “conventional” classification (defined as low, middle and high implants) (Fujimoto et al, 2020; Mortelé et al, 2006; Turner & Fulcher, 2001) and the new proposed quantitative classification (Renzulli, Brocchi, et al, 2021). In particular, according to the new proposed quantitative classification, the EHBD was classified as type 1 (below the 25th percentile, when the CDDP/EHBD ratio is ≤50%), type 2 (between the 25th and 75th percentile, when the CDDP/EHBD ratio is >50% but ≤75%) and type 3 (above the 75th percentile, when the CDDP/EHBD ratio is >75%) (Figure 2b).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has found an association between intrapancreatic low insertion cystic duct and choledocholithiasis [16]. However, a plausible underlying mechanism for how low insertion may trigger stone formation in the common bile duct was not provided.…”
Section: Choledocholithiasismentioning
confidence: 98%
“…For example, a low union of the CD has previously been associated with a higher risk of pancreatitis and even periampullary cancer and this association was ascribed to an anatomy-induced pressure process leading to chemical/bilious irritation [2]; this association is probably supported also by the shorter and lesser exposure of the biliary epithelium to the protective or dilutional effect of peri-biliary mucus glands in the upper biliary tree which happens in the presence of a low union [1]. In addition, previous studies have found an association between low insertion of the CD and choledocholithiasis [10] which can be due to increased retrograde pressure in the CD leading to both bile stagnation and impaired gallbladder emptying. In the present case, however, no calculi were detected on both US and MRCP.…”
Section: Main Textmentioning
confidence: 96%